Expectations of stakeholders regarding home care provision in rural Namibia - Ndatinda lipinge, Scholastika; Botes, A C (Curationis (Pretoria), 2002)
As in many countries, the disease pattern in Namibia has changed, health problems are increasing and outweigh the capacity of the existing health resources. Government health facilities in Namibia have limited capacity to accommodate all sick people, especially those who are chronically and terminally ill. Many hospitals in rural Namibia are overcrowded, patients sleep on the floors and, in some cases, children share beds. Morbidities relating particularly to AIDS, chronic conditions and other physical and emotional disabilities are likely to require long-term home care. In most instances, the health system is also not prepared to provide home care, nor provide the support that is required by the caregivers of disabled, chronically sick people. To ease the burden of care felt by the state at health facilities, the Ministry of Health and Social Services in Namibia has, on several occasions, called upon the community and other stakeholders in health care to assist in caring for their loved ones at home (NBC, 1996; MOHSS, 1996). The purpose of the study was to develop and describe a model for capacity building for quality home care in rural Namibia. This article focuses on the first phase of the bigger study, namely the expectations of stakeholders regarding home care provision in rural Namibia. A qualitative, exploratory and descriptive case study design was used. Five cases were purposively selected and thirty stakeholders were interviewed. Data were analysed using a combination of the approaches of Tesch and Morse and Field. To ensure trustworthiness, triangulation and other measures of Lincoln and Guba were used. The expectations were categorised into structures, process and outcome-related expectations. Stakeholders in rural Namibia appear to have dependency tendencies and still expect all resources and services to be provided by someone else, be it the government, the church, the headman and/or any other non-governmental agencies. There is a need empowerment and capacity building in the community and awareness must be created of the responsibility of the community in dealing with home care provision.